Responsibility Of Doctors In Medical Services To Patients According To Laws And Regulations - Olivia Pusparini; Erikson Sihotang; Ni Ketut Wiratny (Journal of Social Research, 2024)
A doctor's legal responsibility is a doctor's "relationship" to legal provisions in carrying out his profession. The responsibility of a doctor in the field of law is divided into three parts, namely the responsibility of a doctor in the field of civil law (Articles 1365, 1366, 1426) criminal, (Article 322, Article 351, Article 356 of the Criminal Code regarding abuse, Article 359, Article 360, and Article 378 of the Criminal Code regarding acts of fraud and ethical responsibility. Legal protection for patients in health services claiming their rights as regulated in Article 276 of the Health Law, can claim compensation for health workers and/or health providers who cause losses due to errors or negligence of doctors.